Shareholding in the Keiretsu, Japan's Financial Groups - Flath, David (The Review of Economics and Statistics, 1993)
Largest debtholders in keiretsu member companies hold more stock if the companies have high debt-to-equity ratios or have weaker collateral, greater prospects of growth, or unique aspects. All are factors associated with the agency problems of debt that stockholding by a debtholder can help to resolve. The stockholding also induces greater borrowing by these same companies, ceteris paribus. Copyright 1993 by MIT Press.